2021
DOI: 10.1021/acs.biomac.1c00387
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Radical Scavenging Activity and UV Resistance of Lignin Nanoparticles via Surface Mannich Amination toward a Biobased Antioxidant

Abstract: In recent years, lignin specific activities, such as antioxidation and antibacterial and anti-ultraviolet performance, have drawn more and more attention. Nevertheless, the insufficient radical scavenging (antioxidation) activity has become one of the main drawbacks that limits its high-value application. In this study, lignin nanoparticles (LNPs) were prepared via a facile acid treatment strategy. Subsequently, surface amination of LNPs (a-LNPs) was carried out through the Mannich reaction. Specifically, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 53 publications
1
44
0
Order By: Relevance
“…The micromorphologies of LNP and the LNP- g -PLLA copolymer photographed by a transmission electron microscope are shown in Figure . The size of LNP is around 35 nm; meanwhile, the morphology of LNP- g -PLLA displayed that LNP were wrapped by PLLA (around 5 nm in thickness). The particle sizes of LNP before and after modification were also measured by transmission electron microscopy (TEM) and dynamic light scattering (DLS), and the result is presented in Figures S2 and S3.…”
Section: Results and Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The micromorphologies of LNP and the LNP- g -PLLA copolymer photographed by a transmission electron microscope are shown in Figure . The size of LNP is around 35 nm; meanwhile, the morphology of LNP- g -PLLA displayed that LNP were wrapped by PLLA (around 5 nm in thickness). The particle sizes of LNP before and after modification were also measured by transmission electron microscopy (TEM) and dynamic light scattering (DLS), and the result is presented in Figures S2 and S3.…”
Section: Results and Discussionmentioning
confidence: 91%
“…In recent years, the lignin nanoparticles, due to their interesting UV block and anti-oxidative properties, have drawn much attention. The nanosized lignin has been tremendously considered in food packaging, skin cosmetic, and wound dressing biomedical applications. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is mainly composed of three phenylpropane units, containing rich aromatic ring structures, aliphatic, aromatic hydroxyl groups and quinone active groups. [1][2][3] As a byproduct of the chemical industry of forest products, lignin is mainly used as a fuel with low utilization value. In recent years, lignin nanospheres (LNPs) have become a research hotspot and showed great potential applications in drug delivery, electrochemistry, catalysis and other elds.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, biobased EPs have been considered to replace fossil-based alternatives: until now, plenty of bio-renewable feedstock materials, such as epoxidized soybean oils, , itaconic acid, cardanol, , and lignin and its derivatives, have aroused much attention for the preparation of EPs. Although great progress has been made in the preparation of these bio-renewable products, the comprehensive properties of EPs are limited, owing to the specific chemical structure and limited storages of bio-renewable raw materials.…”
Section: Introductionmentioning
confidence: 99%